Systems pathway engineering of Corynebacterium crenatum for improved L-arginine production - Man, Zaiwei (Sci Rep, 2016)
L-arginine is an important amino acid in food and pharmaceutical industries. Until now, the main production method of L-arginine in China is the highly polluting keratin acid hydrolysis. The industrial level L-arginine production by microbial fermentation has become an important task. In previous work, we obtained a new L-arginine producing Corynebacterium crenatum (subspecies of Corynebacterium glutamicum) through screening and mutation breeding. In this work, we performed systems pathway engineering of C. crenatum for improved L-arginine production, involving amplification of L-arginine biosynthetic pathway flux by removal of feedback inhibition and overexpression of arginine operon; optimization of NADPH supply by modulation of metabolic flux distribution between glycolysis and pentose phosphate pathway; increasing glucose consumption by strengthening the preexisting glucose transporter and exploitation of new glucose uptake system; channeling excess carbon flux from glycolysis into tricarboxylic acid cycle to alleviate the glucose overflow metabolism; redistribution of carbon flux at α-ketoglutarate metabolic node to channel more flux into L-arginine biosynthetic pathway; minimization of carbon and cofactor loss by attenuation of byproducts formation. The final strain could produce 87.3 g L(−1) L-arginine with yield up to 0.431 g L-arginine g(−1) glucose in fed-batch fermentation.